Subcuticular Barbed Suture and Skin Glue Wound Closure Decreases Reoperation and Length of Stay in Geriatric Hip Fractures When Compared With Staples. (4th October 2021) - Zhao, Emily; Tarkin, Ivan S.; Moloney, Gele B.
Abstract : Introduction: Patients with geriatric hip fracture are notoriously frail and at risk for complications. Persistent postoperative wound drainage can lead to prolonged hospital stay, increased risk for infection, and need for revision surgery. The purpose of this study was to determine the effect of wound closure technique, barbed monofilament subcuticular suture and skin glue versus staples on rates of intervention for wound drainage and length of hospital stay after geriatric hip fracture fixation. Methods: A retrospective review of isolated hip fractures in patients older than 60 years at a single institution over a 3-year period was done. Hip fractures included femoral neck, intertrochanteric, and subtrochanteric femur fractures treated with internal fixation or arthroplasty. Skin closure technique, at the discretion of the operating surgeon, included either barbed subcuticular monofilament suture and skin glue or staples. Charts and radiographs were reviewed to determine patient characteristics, Charlson Comorbidity Index, type of wound closure, length of stay, and interventions for persistent wound drainage. Results: There were 175 patients in the barbed suture and skin glue group and 211 patients in the staples group. The barbed suture group had an average postsurgical length of stay of 5.0 days which was significantly lower than the staples group (7.0 days, P < 0.00001). In the staples group, 17 patients (8%) required incisional negative pressure wound therapy due to wound drainage with five patients (2.4%) returning to the operating room secondary to persistent wound drainage. No patients were observed in the barbed suture group that required intervention for wound drainage. Discussion: Barbed suture and skin glue closure is associated with markedly shorter hospital stay and fewer interventions for wound drainage when compared with staples after surgical treatment of geriatric hip fractures.